The computational implementation of a platform of relative identity-by-descent scores algorithm for introgressive mapping - Cui, Bo; Guo, Zhongxu; Cao, Hongbo; Calus, Mario; Zhang, Qianqian (Frontiers in Genetics, 2023)
With development of genotyping and sequencing technology, researchers working in the area of conservation genetics are able to obtain the genotypes or even the sequences of a representative sample of individuals from the population. It is of great importance to examine the genomic variants and genes which are highly preferred or pruned during the process of adaptive introgression or long-term hybridization. Here, we as the first develop a platform with computational integration of a relative Identity by Descent (rIBD) scores algorithm for introgressive mapping. The rIBD algorithm is designed for mapping the fine-scaled genomic regions under adaptive introgression between the source breeds and the admixed breed. Our rIBD calculation platform provides compact functions including reading input information and uploading of files, rIBD calculation, and presentation of the rIBD scores. We analyzed the simulated data using the rIBD calculation platform and calculated the average IBD score of 0.061 with the standard deviation of 0.124. The rIBD scores generally follow a normal distribution and a cut-offs of 0.432 and -0.310 for both positive and negative rIBD scores are derived, to enable to identify genomic regions showing significant introgression signals from the source breed to the admixed breed. A list of genomic regions with detailed calculated rIBD scores are reported, and all the rIBD scores for each of the considered windows are presented in plots on the rIBD calculation platform. Our rIBD calculation platform provides a user-friendly tool for the calculation of fine-scaled rIBD scores for each of the genomic regions to map possible functional genomic variants due to adaptive introgression or long-term hybridization.